The population structure and ecology of the Antarctic Scallop, Adamussium colbecki in Terra Nova Bay (Ross Sea, Antarctica) - CATTANEO VIETTI R.; CHIANTORE, MARIACHIARA; ALBERTELLI, GIANCARLO (1997)
One of the main purposes of the core project “Ecology and Biogeochemistry of the Southern Ocean” (Italian Antarctic Programme-PNRA) is to understand the utilization and ultimate fate of the organic matter sedimenting through the water column and its influence in the structure of the macrobenthic assemblages. At Terra Nova Bay (Ross Sea), the scallop Adamussium colbecki (Smith, 1902) constitutes large beds up to 70-80 m depth. The importance of this population in the local community structure requires a closer examination of its structure and dynamics, in order to assess its role in the coastal organic matter flux, and for this reason it has been studied during several years (1987-92) in areas close to the Italian Station and particularly in the Summer 1993/94. Its high density (up to 60 ind m -2) and biomass (up to 120 g m -2 dry weight of soft tissues) values are probably linked to slow growth rate and reduced reproductive capacities. X-ray studies on the shell confirmed the slow growth rate of this species, which averages about 0.8 cm yr -1. The analysis of the ratio between length and height of the shell (generally ~ 1) shows a significative inversion at the age of maturity, when the byssally attached juveniles become free from the adult valves. A comparison of the gonadosomatic index in the population between December and January suggests that sexual maturity is reached late in this season and is strongly related to the water column food supply consequent to the phytoplankton bloom. Comparing the size-frequency distribution of this population in different years, it is possible to observe a cohort gap, shifting through the study period, and probably caused by unsuccessful recruitments from 6 to 9 years before 1994. Slow growth rate and intermittent recruitment suggest that an eventual commercial exploitation of this species, abundant but patchly distributed in a narrow bathymetric range, would quickly result in overfishing and commercial failure.